Incinerator in Malaysia : really needs? - Abdul Rahman, Haliza (International Scientific Academy of Engineering & Technology, 2013)
Increasing population, tremendous urbanisation growth and rapid economic growth influence directly the Municipal Solid Waste generation in Malaysia. Thus, incineration is one of the considered methods of waste treatment that is quickly attracting the municipal authorities’ attention in this country because incineration solves many of the problems so common to other methods of municipal garbage disposal. The advantages of incinerator plant including will not have rodent problems, produce bad odours, require large plots of land or require many employees. Therefore, incineration will become one of the best practical choices in treating municipal solid wastes in Malaysia in the near future due to the various constraints such as limited landfill sites, immature recycling and biological treatment infrastructures. However, the advantages and disadvantages of this method need to study deeply and properly before installing such system in Malaysia.